Comparisons of Performance of Non-Governmental Organization and Gram Panchayats in Disaster Management - Mondal, Debabrata; Chowdhury, Sarthak; Basu, Debabrata (Indian Journal of Extension Education, 2016)
Disasters like floods, cyclones, droughts and earthquakes are increasing in India and in almost all parts of the earth due to  environmental degradation, deforestation, increasing population, global warming, nuclear explosions, and air pollution.  There is also worldwide concern to mitigate the growing incidence of disaster and their toll on human life, property, and  environment. The role of Panchayats (local self governing institutions) is important in view of their proximity to the local  community, coverage and engaging people's participation on an institutionalized basis. NGOs are organizations that are  nonprofit making, voluntary and independent of government, engaged in activities concerning various societal and  developmental issues. The role of the NGOs during a disaster is to have quick response and to try and save as many lives as  it can with the given funds. Astudy was undertaken in cyclone Aila affected areas in West Bengal on analysis of the role of  Non Governmental Organization and Gram Panchayats on disaster management. The main role performed by the NGOs  were providing relief materials, organizing health camp, involved in rescue operation, arranging temporary shelters and  so on. On the other hand the major functions of G.P during the post-disaster were identification of victims for  compensation, relief and rehabilitation work, monitoring and supervision of relief works as well as damage assessment.  The data were collected in the month of October 2013 to March, 2014 to attain the objective of the study. A total 150  respondents were selected purposively as the respondents. The data were processed into percentage, mean score and t test. The findings of the study indicated that, the people of the disaster affected area should inform the details of the  disaster sufficiently ahead.
Keywords: Disaster management; NGOs; Gram Panchayats; Comparisons; relief and rehabilitation